Effects of Pastoralism and Rabbits on the Economy and Culture of the Diyari People of North‐Eastern South Australia. (29th May 2015) - Cooke, Brian
Abstract : The contraction of Aboriginal people from South Australian deserts is associated with European pastoral expansion. Confined to areas near water, livestock damaged vegetation locally, but introduced rabbits, not reliant on drinking water, spread well beyond pastoral settlement. Thus, rabbits caused almost universal desertification and were an equal factor in disrupting the former food web that sustained Aboriginal people. Within 30 years of the rabbits' arrival, important totemic animals like rabbit bandicoots had disappeared, leaving the people not only short of traditional game but also culturally bereft. A comparative economic approach to Aboriginal totemism explores changes in both ecological and cultural contexts.